Character and frequency of postoperative complications at surgical treatment of arothae aneurism - V. I. Kravchenko (Ukrainian Journal of Cardiovascular Surgery, 2018)
Surgeries on ascending aorta and aortic arch due to aneurysms remain the most complicated problem in cardiovascular surgery. The research presents the analysis of postoperative complications, depending on the methods of protection of the brain and the time of execution, the results of surgical treatment with reducing mortality from 28% to 3.9% are presented.Purpose. Analysis of postoperative complications of surgical treatment of aneurysms of the arc at different stages of our surgical experience, and demonstration of general results of surgical treatment of aortic arch aneurysms.Materials and methods. During 1994–2016, we operated 317 patients with an ascending aneurysms and arch (or just arches) of the aorta.Conclusions. Thus, observing the general results of the work, we note that postoperative complications at stage I developed in 64% of cases operated with a reducing down to 31.7%, in the second stage and down to 20 (8.7%) at the final stage (p<0.05). Hospital mortality is 8.5%, at the first stage it was 28%, with a decrease to 17.5% at stage II and 3.9% at the final stage of work.